Penentuan Persamaan Distribusi Temperatur Udara Dalam Ruang Annulus Pada Daerah Sub-Layer Laminar Dengan Metoda Regresi - Permatasari, Rosyida; Riyono, Joko (MESIN, 2007)
Determination of Air Temperature Distribution Equation in Annulus Room on LaminarSub Layer Theretorey. Laminar sub-layer is a very thin region near the wall has a laminar character andthe viscous action and heat transfer take place under circumstances like those in laminarflow. ^ Havingobtained a knowledge of the temperature distribution, the heat transfer rate from a heated surface to afluid which isforced over it may be determined. The temperature distribution is obtained by leastsquaremethod. Andthe observation data is closed by exponentialregression equation.